Intravascular embolization of a direct orbital arteriovenous fistula: case report and review of the literature - Cheng, Olivia T.; Chung, Stella Y.; Wilseck, Jeffrey M.; Kahana, Alon (Frontiers in Ophthalmology, 2025)
Orbital arteriovenous fistulas are exceedingly rare and present a unique challenge due to difficulties with access. We report a case of a patient with an acute progressive direct orbital arteriovenous fistula causing orbital compartment syndrome and compressive optic neuropathy. He underwent medial orbital decompression followed immediately by direct cannulation of the vascular anomaly, through which two separate fistulas were embolized under fluoroscopic guidance.